2021
DOI: 10.15252/embj.2021107839
|View full text |Cite
|
Sign up to set email alerts
|

Non‐genetic and genetic rewiring underlie adaptation to hypomorphic alleles of an essential gene

Abstract: Adaptive evolution to cellular stress is a process implicated in a wide range of biological and clinical phenomena. Two major routes of adaptation have been identified: non-genetic changes, which allow expression of different phenotypes in novel environments, and genetic variation achieved by selection of fitter phenotypes. While these processes are broadly accepted, their temporal and epistatic features in the context of cellular evolution and emerging drug resistance are contentious. In this manuscript, we g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 58 publications
(68 reference statements)
0
1
0
Order By: Relevance
“…The likely many close protein–protein interactions involved in FAZ assembly and function suggest that compensatory changes in other interacting and non‐interacting proteins may well be expected in this system. The exact nature of these changes has still to be identified, and whether they result from genomic and/or transcriptomic changes (Targa et al., 2021 ). Work in yeast showed that there was a preference for changes to genes functionally related to the deleted gene, so there is the potential that these mutants harbour changes in genes important for FAZ assembly and cell morphogenesis (Farkas et al., 2022 ; Helsen et al., 2020 ; Szamecz et al., 2014 ; Venkataram et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…The likely many close protein–protein interactions involved in FAZ assembly and function suggest that compensatory changes in other interacting and non‐interacting proteins may well be expected in this system. The exact nature of these changes has still to be identified, and whether they result from genomic and/or transcriptomic changes (Targa et al., 2021 ). Work in yeast showed that there was a preference for changes to genes functionally related to the deleted gene, so there is the potential that these mutants harbour changes in genes important for FAZ assembly and cell morphogenesis (Farkas et al., 2022 ; Helsen et al., 2020 ; Szamecz et al., 2014 ; Venkataram et al., 2016 ).…”
Section: Discussionmentioning
confidence: 99%